Cuidado tópico da úlcera do pé diabético : aplicativo móvel para subsídio à tomada de decisão - Colodetti, Rafael (2018)
Introduction: Diabetic foot ulcer precedes most amputations, implying a major socioeconomic impact and a serious public health problem. Nursing has a crucial role in the decision-making process involved in the care of this type of injury, from a wellconducted intervention at the most appropriate time for obtaining healing. It is essential to implement a systematized assistance based on evidence, with information technology and communication a tool capable of providing the articulation between theory, practice and research. Objectives: To develop application for mobile devices that assist nurses in the process of decision making of the topical treatment of diabetic foot ulcer; validate th developed mobile application. Methods: Methodological study subsidized by Norm ABNT ISO/TR 16982:2014, carried out in four steps: Step 1) Definition of requirements and elaboration of the conceptual map of the application; Step 2) Generation of implementation and prototyping alternatives; Step 3) Tests; and Step 4) Implementation. All the stages of the research were developed at the Federal University of Espírito Santo (UFES) in a partnership with the Laboratory and Observatory of Design Ontology (LOOP)/Design course. For the development of the application, we used Nativescript software for Android platform and the organization gave itself in iterative design cycles. Performed usability tests with 18 participants, considering the heuristics of Nielsen and due adaptations for mobile devices. Results: The application offers current information about the diabetic foot wound, such as concept, evaluation, treatment principles, clinical recommendations for better healing and special dressings for topical care. The heuristic evaluation and testing provided important information for its validation and it is demonstrated that it is easy to use, understanding its concept and application, providing clear help to the user. The technology tool will be available in the Google Play Store. Conclusion: The methods established for development and validation have proved appropriate to achieve the proposed objectives. With the offer of this technological tool is expected to contribute to the best care of the diabetic foot wound, as well as to a nursing practice based on evidence.